Identification of N‐Arylated NH125 Analogues as Rapid Eradicating Agents against MRSA Persister Cells and Potent Biofilm Killers of Gram‐Positive Pathogens. (16th January 2017) - Abouelhassan, Yasmeen; Basak, Akash; Yousaf, Hussain; Huigens, Robert W.
Abstract: Bacterial biofilms housing dormant persister cells are innately tolerant to antibiotics and disinfectants, yet several membrane‐active agents are known to eradicate tolerant bacterial cells. NH125, a membrane‐active persister killer and starting point for development, led to the identification of two N‐arylated analogues (1 and2 ) that displayed improved biofilm eradication potencies compared to the parent compound and rapid persister‐cell‐killing activities in stationary cultures of methicillin‐resistant Staphylococcus aureus (MRSA). We found1 and2 to be superior to other membrane‐active agents in biofilm eradication assays, with1 demonstrating minimum biofilm eradication concentrations (MBEC) of 23.5, 11.7, and 2.35 μm against MRSA, methicillin‐resistant Staphylococcus epidermidis (MRSE), and vancomycin‐resistant Enterococcus faecium (VRE) biofilms, respectively. We tested our panel of membrane‐active agents against MRSA stationary cultures and found1 to rapidly eradicate MRSA stationary cells by 4 log units (99.99 %) in 30 min. The potent biofilm eradication and rapid persister‐cell‐killing activities exhibited by N‐arylated NH125 analogues could have significant impact in addressing biofilm‐associated problems. Abstract : Biofilm busters : We have discovered and evaluated a series of N‐arylated NH125 analogues that display potent biofilm‐eradicating activity against multiple Gram‐positive pathogens and rapidly kill MRSA persister cells in stationary cultures. These analogues are promising new broad‐spectrum agents against bacterial resistance.